2014
DOI: 10.1016/j.envpol.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Particle pollution in Rio de Janeiro, Brazil: Increase and decrease of pro-inflammatory cytokines IL-6 and IL-8 in human lung cells

Abstract: Particle pollution from urban and industrialized regions in Rio de Janeiro (RJ), Brazil was analyzed for toxic and pro-inflammatory (cytokines: IL-6, IL-8, IL-10) responses in human bronchial epithelial cells. Trace elements contribution was studied. Airborne particulate matter was collected at: three industrial sites Ind-1 (PM10) and Ind-2a and 2b (PM2.5); Centro urban area (PM10) and two rural sites (PM2.5, PM10). PM10 acetone extracts were toxic and did not elicit cytokine release; aqueous extracts were les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 42 publications
1
29
0
6
Order By: Relevance
“…The specific abundance, mixture and combination of metals can induce or alter cytokine secretions by cells. Cytokine release suppressed by metals can affect the signaling for a biological response (Rodriguez-Cotto et al, 2014). Both polar and nonpolar extracts were evaluated for cytokine secretion (IL-6 and IL-8) by BEAS-2B after 24 h extract exposure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The specific abundance, mixture and combination of metals can induce or alter cytokine secretions by cells. Cytokine release suppressed by metals can affect the signaling for a biological response (Rodriguez-Cotto et al, 2014). Both polar and nonpolar extracts were evaluated for cytokine secretion (IL-6 and IL-8) by BEAS-2B after 24 h extract exposure.…”
Section: Resultsmentioning
confidence: 99%
“…This is an opposite effect of what is normally reported for particulate matter extracts and its metal contents. Particulate matter samples from Río de Janeiro, Brazil were previously analyzed showing an increase and decrease in pro-inflammatory cytokines (Rodríguez-Cotto et al, 2014). The effect on IL-8 was similar to that of IL-6 with B100 (50 μg mL -1 ) sample, however, it was more profound because the levels are significantly higher with DF (50 μmol L -1 ) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Mostafavi et al19 have shown that long-term exposure to NOx was associated with a lower rate of IL2, IL8, IL10 and TNFα. Finally, a toxicological study in Rio de Janeiro showed that suspended particles can either increase or decrease the secretion of cytokines in vitro in the case of human bronchial epithelial cells 20. To date, the relationship between exposure to air pollution and cytokines in rural settings has been rarely investigated 15.…”
Section: Introductionmentioning
confidence: 99%